Morbidity and mortality in patients over 90 years of age following posterior stabilization for acute traumatic odontoid type II fractures: a retrospective study with a mean follow-up of three years - Issa, Mohammed; Kiening, Karl; Unterberg, Andreas; Scherer, Moritz; Younsi, Alexander; Fedorko, Stepan; Oskouian, Rod J.; Chapman, Jens R.; Ishak, Basem (Journal of Clinical Medicine, 2021)
Odontoid type II fractures represent the most common cervical spine injuries in the elderly. The decision for surgical treatment in very elderly patients is still controversial. The aim of this study was to assess morbidity and mortality in patients over 90 years of age undergoing CT-guided posterior stabilization for unstable odontoid type II fractures. A total of 15 patients with an acute traumatic odontoid type II fracture who received surgical treatment for unstable odontoid type II fractures were retrospectively analyzed. Complications, morbidity, and mortality as well as length of ICU and hospital stay were determined. Clinical follow-up evaluation was based on outpatient presentation and information from family members and general practitioners. Finally, we conducted a comparison of complications rates between patients over 90 years of age and patients between 65 and 89 years old with a type II odontoid fracture after CT-guided posterior stabilization in our institution. The mean age was 91.4 years. Patients were predominately female (87%). In-hospital deaths did not occur. The average length of the hospital stay was 13.4 days and 1.9 days for the ICU. Blood transfusion was necessary in two patients (13%). Two patients (13%) developed urinary tract infection, one patient (7%) a delirium, and another epistaxis (7%). One patient (7%) developed pneumonic sepsis and fully recovered within several weeks. The mean follow-up was 36 months (range 9-72 months). Implant-related complications developed in one patient (7%). Five patients died during the follow-up period, with an average time to death of 26.6 months. Postoperative bracing was not needed in any of the patients. Posterior stabilization of unstable odontoid fractures type II using CT-guided navigation in patients over 90 years of age is a safe and effective procedure with low complications and mortality rates.